Product Placement en la red social de Instagram. caso: Natalia Merino-Cinnamon Style - Trinidad Alvarado, Mayle Yajaira (2021)
With the use of the content analysis method, this qualitative research seeks to answer the question: “In what way does influencer Natalia Merino - Cinnamon Style apply product placement in her Instagram posts to promote a product and/or service?” Various topics were developed in relation to influencers and advertising, on social networks. Likewise, the subject of product placement, its definitions and classification were investigated. Finally, an analysis of the case study "Natalia Merino - Cinnamon Style" was carried out on the publications, in which the presence of product placement and the discourse used in them is evidenced. To do this, the sample of 113 publications was analyzed, corresponding to the @cinnmonstyle account on Instagram during 2019. It's concluded that the type of Product Placement that stands out the most in the content of the influencer is the Dynamic and that their speech is focused on their followers, points that they develop with detail in the discussion.